2018
DOI: 10.1002/1878-0261.12187
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA CASC15 regulates gastric cancer cell proliferation, migration and epithelial mesenchymal transition by targeting CDKN1A and ZEB1

Abstract: Long non‐coding RNA (lncRNA) is responsible for a diverse range of cellular functions, such as transcriptional and translational regulation and variance in gene expression. The lncRNA CASC15 (cancer susceptibility candidate 15) is a long intergenic non‐coding RNA (lincRNA) locus in chromosome 6p22.3. Previous research shows that lncRNA CASC15 is implicated in the biological behaviors of several cancers such as neuroblastoma and melanoma. Here, we aimed to explore in detail how CASC15 contributes to the growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 44 publications
4
75
0
1
Order By: Relevance
“…Several lncRNAs have been documented to participate in various biological processes, especially in tumorigenesis 6–8 . Multiple lncRNAs have been reported to regulate cell proliferation, migration, invasion, and apoptosis in GC cells, such as GHET1, HOTAIR, UCA1, and CASC15 among others 9–12 . LncRNAs can act as oncogenes or tumor suppressors in GC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lncRNAs have been documented to participate in various biological processes, especially in tumorigenesis 6–8 . Multiple lncRNAs have been reported to regulate cell proliferation, migration, invasion, and apoptosis in GC cells, such as GHET1, HOTAIR, UCA1, and CASC15 among others 9–12 . LncRNAs can act as oncogenes or tumor suppressors in GC.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Multiple lncRNAs have been reported to regulate cell proliferation, migration, invasion, and apoptosis in GC cells, such as GHET1, HOTAIR, UCA1, and CASC15 among others. [9][10][11][12] LncRNAs can act as oncogenes or tumor suppressors in GC.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] In addition, studies have found that some aberrant regulations between microRNA (miRNA) and mRNA have an important impact on the progression of gastric cancer. For the abnormal regulations between long noncoding RNA (lncRNA) and messenger RNA (mRNA), some studies have shown that lncRNA can promote the proliferation and metastasis of gastric cancer cells by regulating the differentially expressed mRNA.…”
mentioning
confidence: 99%
“…For the abnormal regulations between long noncoding RNA (lncRNA) and messenger RNA (mRNA), some studies have shown that lncRNA can promote the proliferation and metastasis of gastric cancer cells by regulating the differentially expressed mRNA. [5][6][7] In addition, studies have found that some aberrant regulations between microRNA (miRNA) and mRNA have an important impact on the progression of gastric cancer. 2,4,8 For the relationships of lncRNA-miRNA, although lncRNA and miRNA do not have the function of encoding proteins, the mutual regulations between lncRNA and miRNA can lead to abnormal expression of some signaling pathways and have an important influence on the growth, metastasis, metabolism, and apoptosis of gastric cancer cells.…”
mentioning
confidence: 99%
“…The ability of BC cells to metastasize has been correlated with the acquisition of an EMT phenotype (Chaffer, San Juan et al, 2016). Further, previous works suggested that WDR5 might regulate metastasis formation by inducing EMT in various cancers , Malek et al, 2017, Wu, Xiang et al, 2018a. We tested whether WDR5 silencing could reduce the migratory ability of BC cells by directly inhibiting EMT.…”
Section: Wdr5 Silencing Inhibits Emt In Breast Cancermentioning
confidence: 96%